Establishment of a CIB1 knockout human pluripotent stem cell line via CRISPR/Cas9 genome editing technology - Tingyu Gong; Dandan Liu; Xiaochen Wang; Danni Zhou; Ling Tang; Hao Wang; Jun Su; Ping Liang (Stem Cell Research)
Calcium- and integrin-binding protein 1 (CIB1) has a diverse role in many different cell types and processes, including calcium signaling, migration, adhesion, proliferation, and survival. It is associated with cancer, cardiovascular disease and male infertility. Here, CRISPR/Cas9 genome-editing technology was employed to establish a CIB1 knockout human embryonic stem cell line, which exhibited normal pluripotency and karyotype.